Prevalence of HPV, cytological abnormalities, and impact of the HPV vaccine in Mexico: a Nationwide Study of 596,944 womenResearch in context - Abraham García-Gil; Marco Antonio Luna-Ruiz-Esparza; José Luis Moreno-Camacho; Diana Yadira Calva-Espinosa; Ludwing Erick González-Mena; Luis Fernando Hernández-Lezama; Pablo Kuri-Morales; Juan Carlos Balcázar-Rodríguez; Abraham Campos-Romero; Jonathan Alcántar-Fernández (The Lancet Regional Health. Americas)
Summary: Background: Cervical cancer (CC) remains a significant public health challenge worldwide and is the second leading cause of cancer-related death in women in Mexico. Although CC is highly preventable, effective implementation of screening programs to detect women with precancerous lesions is crucial to reduce its burden. This study evaluated HPV infection, its correlation with cytological abnormalities, and the impact of HPV vaccination in 596,944 women from all 32 states of Mexico. Methods: Samples were processed using a fully automated molecular biology laboratory setup (Roche Cobas prime - Cobas 6800), and cytotechnologists assessed cytological outcomes. Findings: The highest prevalence of HPV infection was observed among women under the age of 25, with 23,615 individuals (37.4%) testing positive. This was primarily attributable to infections with the pooled high-risk HPV genotypes included in the assay (HPV31, 33, 35, 39, 45, 51, 52, 56, 58, 59, 66, and 68), which accounted for 22,792 cases (36.1%). In contrast, HPV16 and HPV18 were most prevalent among women aged 25–34 years, with 7251 (5.21%) and 3281 (2.36%) infections, respectively. Low-grade squamous intraepithelial lesion (LSIL) was the most frequently detected cytological abnormality, identified in 15,411 cases (2.6%), and was predominantly associated with the pooled HPV genotypes (73.7%). A two-dose HPV vaccination regimen conferred strong protection against HPV16 (odds ratio [OR] = 0.21) and HPV18 (OR = 0.33), but did not significantly reduce the prevalence of infection with the pooled HPV genotypes (OR = 0.98). Interpretation: The notable carcinogenic potential of the HPV POOL underscores the need for broader vaccine formulations. Adopting a nonavalent vaccine in future campaigns, expanding screening coverage, and reinforcing sexual education for younger women are key measures to help policymakers mitigate the impact of CC in Mexico. Funding: This work was funded by Salud Digna.